Experimental investigation of an airfoil response under stall-induced pitching oscillations - Pereira, Daniel A.; Vasconcellos, Rui M. G. [UNESP]; Marques, Flávio D. (American Institute of Aeronautics and Astronautics (AIAA), 2016)
In this work, an investigation on the embedded dynamics of experimental aeroelastic signals of an airfoil under the influence of stall-induced oscillations is presented. Helicopter blades or wind turbines are examples of real aeroelastic surfaces that severely vibrate in stall conditions, leading to problems that motivates this research. Despite significant efforts to model the aerodynamics associated with the stall phenomenon, non-linear aeroelastic behavior prediction and analysis in such flow regime remains a challenge. This modeling requires proper knowledge of the physical events during stall regime, such knowledge can be better attained from experimental data. In this work a pitching airfoil is tested in a wind tunnel model. The aeroelastic signals are acquired using an optical angular encoder and the data is evaluated applying techniques from time series theory as the state space reconstruction, Poincaré sections and bifurcation analysis. The method of Singular Value Decomposition (SVD) is used to reconstruct the state space, revealing indications to possible bifurcations and complex dynamics. Changes in amplitudes of stall-induced oscillation due to airspeed and preset angles increases were also investigated. The results show that the airfoil presents sustained periodic and limit cycle oscillations at high angles of attack due to the stall influence. For the different preset angles, the appearance of the second bifurcation changes the range of oscillations, from asymmetric to symmetric with a significant increase in the amplitude. It is shown that the system complexity is mostly dependent on the aerodynamic flow conditions that override possible nonlinear structural effects and direct the airfoil to present significant stall-induced oscillations.